Sweden : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
This Selected Issues paper discusses measures taken to enable timely macroprudential action in Sweden. The Swedish financial supervisory authority has adopted a number of macroprudential measures under its mandates for financial stability and consumer protection. The supervisory authority imposed a loan-to-value limit of 85 percent for new mortgage loans in 2010, with the soundness principle as the legal basis for this measure. Under its financial stability mandate, it also set a floor on risk weights for Swedish mortgages, which was raised from 15 percent to 25 percent in September 2014. Following an expansion of the regulatory toolkit, a range of capital buffers have also been established and subsequently expanded.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet